Stanisław Brzozowski – to think radically - Kędziora, Krzysztof (Hybris, 2014)
Stanisław Brzozowski is one of the most radical philosophers. Radicalism of his thought involves not only the idea of fundamental social change, but also the reinterpretation of some philosophical concepts. Two main concepts are nature and history. They are reinterpreted in order to show their human origins. According to Brzozowski nature and history are human constructions, namely they are set by human praxis. Brzozowski’s understanding changed over the time. In my article I focus on two phases of Brzozowski’s thought. The first is Kantian and Fichtean. At that point Brzozowski interprets human praxis as moral act. The second one is Marxian. At that point human praxis is understood as labour.